Identification of a Putative Enhancer RNA for EGFR in Hyper-Accessible Regions in Esophageal Squamous Cell Carcinoma Cells by Analysis of Chromatin Accessibility Landscapes - Choi, Sangyong; Sathe, Adwait; Mathé, Ewy; Xing, Chao; Pan, Zui (Frontiers in Oncology, 2021)
Abnormal genetic and epigenetic modifications play a key role in esophageal cancer. By Assay for Transposase-Accessible Chromatin by sequencing (ATAC-seq), this study compared chromatin accessibility landscapes among two esophageal squamous cell carcinoma (ESCC) cell lines, KYSE-30 and KYSE-150, and a non-cancerous esophageal epithelial cell line, HET-1A. Data showed that hyper-accessible regions in ESCC cells contained genes related with cancer hallmarks, such as epidermal growth factor receptor (EGFR). Multi-omics analysis and digital-droplet PCR results demonstrated that several non-coding RNAs in EGFR upstream were upregulated in ESCC cells. Among them, one appeared to act as an enhancer RNA responsible for EGFR overexpression. Further motif analysis and pharmacological data suggested that AP-1 family transcription factors were able to bind the hyper-accessible regions and thus to regulate cancer cell proliferation and migration. This study discovered a putative enhancer RNA for EGFR gene and the reliance of ESCC on AP-1 transcription factor.